When cardiac surgery comes to its limits: a case report of pericardial mesothelioma invading the myocardium. Issue 7 (7th July 2021) - Pölzl, Leo; Hirsch, Jakob; Mayr, Agnes; Uprimny, Christian; Oberhuber, Georg; Zwick, Hansjörg J; Müller, Ludwig; Pölzl, Gerhard
Abstract: Background: Primary pericardial mesothelioma (PPM) is a rare form of highly aggressive cancer. Many patients are diagnosed only at an advanced stage. Therefore, the overall survival rate is poor with a median survival of 3 months. In some rare cases, the PPM infiltrates the myocardium causing lethal myocardial dysfunction. Case summary: A 66-year-old patient was transferred to our centre with the provisional diagnose of pericarditis of unknown origin. Using extensive cardiac imaging [echocardiography, computed tomography (CT), positron emission tomography–CT, cardiac magnetic resonance imaging, left and right heart catheterization, coronary angiography], PPM was finally diagnosed. After consultation with the oncologists, the heart team decided to resect the tumour first due to impaired haemodynamics and then initiate adjuvant chemotherapy. Intraoperatively, myocardial infiltration of the tumour became apparent, which was not detected preoperatively despite intensive imaging. Complete resection of the PPM was not possible and effective decompression of the ventricle could not be achieved. The patient died on the first postoperative day. Discussion: Surgical therapy is indicated in many forms of cardiac tumours. However, when a tumour invades the myocardium, surgery often comes to its limits. In this case, myocardial invasion of PPM could not be detected despite extensive imaging. We therefore suggest that possible myocardial infiltration by PPM, and thus potential limitations of cardiac surgery, should be considered independently of imaging results when therapeutic options are discussed.